Understanding Resilience And Coping In Depression And Ocd: Insights From A Clinical Sample - Tiwari , Samyak; kumar , Ankit; Qavi , Danish (Journal of Neonatal Surgery, 2025)
Background: Obsessive-Compulsive Disorder (OCD) and Depression are among the most prevalent mental health conditions globally. Both disorders differ in symptomatology but share common psychological constructs such as resilience and coping mechanisms that influence prognosis and functioning. Aim and Objective: To evaluate and compare resilience and coping mechanisms among individuals diagnosed with OCD and Depression. Material and Methods: A cross-sectional analytical study was conducted at a tertiary care centre involving 100 participants—50 with depression and 50 with OCD—diagnosed per ICD-10 criteria. Sociodemographic data were collected, and participants were assessed using the Brief Resilience Scale (BRS) and the Brief COPE Inventory. Statistical analysis was performed using SPSS version 29.0.1.0, with significance set at p<0.05. Results: In the present study emotion-focused coping was predominantly used by depressed patients (56%), whereas OCD patients mostly employed avoidant coping strategies (60%), a difference that was statistically significant (p=0.001). The mean resilience score was significantly higher in depressed individuals (3.1±0.7) compared to those with OCD (2.2±0.6) (p<0.0001). No significant difference was observed in problem-focused coping between the two groups. Conclusion: Depressive patients demonstrated higher resilience and a preference for emotion-focused coping, while OCD patients relied more on avoidant strategies and exhibited lower resilience. These findings underscore the importance of tailored psychotherapeutic approaches that enhance adaptive coping and resilience in both groups